Evaluation of farmers’ knowledge on the rare Abyssinian pea (Pisum sativum var. abyssinicum) landraces of Ethiopia (Biodiversitas Journal of Biological Diversity, 2018)
Gebreegziabher BG, Tsegay BA. 2018. Evaluation of farmers’ knowledge on the rare Abyssinian pea (Pisum sativum var. abyssinicum) landraces of Ethiopia. Biodiversitas 19: 1851-1865. Abyssinian pea (Pisum sativum var. abyssinicum A. Braun) is a rare and problematic taxon requiring evaluation of present farmers’ local knowledge. Cross-sectional data were collected from 444 respondents and analyzed using SPSS software. Descriptive statistics was used; one way ANOVA for significance test of variance and Exhaustive CHAID growth method for predictions. Prediction results showed that the crop requires about two good rains, Nitisol soils and about 21-30 kg ha-1seeding rate. The flowering to maturity time ranges 11?2 to 21?2 months depending on the agroecology (highland or lowland), with a yield of about 300-400 kg ha-1on average. The crop distribution is currently limited to three to four districts and sown after other crops are harvested. Major factors hindering its distribution are agro-ecological suitability, lack of intervention and preference of high yielding pea varieties. The crops’ inferiority in yield and pest susceptibility is the main reason for less extensive awareness on the crop. Though inferior in yield and susceptible to pest, farmers still prefer to grow the crop because of its marketability for local exchange and consumption. The core production problems currently remarked by farmers are expensive price of the seed to buy and small land holding.
Keywords: Agronomic descriptors; indigenous knowledge; seeding rate; soil type; yield